Investigating relationships between motivation and loyalty in the context of physical recreation - Barlas, Achilleas; Kouthouris, Charilaos (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The concept of motivation is very important for participation in recreation. There are three types of motivation: intrinsic motivation, extrinsic motivation and amotivation. The present study investigates consumer behavior issues related to the practice of mini football in Greece. Aim of Study. The study aimed specifically to: a) identify the most important motivation factors that drive individuals to participate in mini football; and b) investigate the predictability of motivation factors towards consumer loyalty. Material and Methods. 150 Greek men participated in the study and were asked to fill in a survey questionnaire. A path analysis method was used to assess the impact of motivation on loyalty. Results. The most important motivation type was extrinsic motivation comprising items related to enjoyment. The path analysis revealed the importance of extrinsic motivation and amotivation for predicting participants’ sport loyalty. Conclusions. The results of the present study can help managers of sport centers understand the significance of mini-football as a recreational activity
Keywords: motivation; mini football; loyalty; sport recreation; customer behavior